Antisense Oligonucleotide-Mediated Reduction of HDAC6 Does Not Reduce Tau Pathology in P301S Tau Transgenic Mice - Valencia, Antonio; Bieber, Veronica L. Reinhart; Bajrami, Bekim; Marsh, Galina; Hamann, Stefan; Wei, Ru; Ling, Karen; Rigo, Frank; Arnold, H. Moore; Golonzhka, Olga; Hering, Heike (Frontiers in Neurology, 2021)
Acetylation of tau protein is dysregulated in Alzheimer’s Disease (AD). It has been proposed that acetylation of specific sites in the KXGS motif of tau can regulate phosphorylation of nearby residues and reduce the propensity of tau to aggregate. Histone deacetylase 6 (HDAC6) is a cytoplasmic enzyme involved in deacetylation of multiple targets, including tau, and it has been suggested that inhibition of HDAC6 would increase tau acetylation at the KXGS motifs and thus may present a viable therapeutic approach to treat AD. To directly test the contribution of HDAC6 to tau pathology, we used an antisense oligonucleotide (ASO) directed against HDAC6 mRNA to reduce its expression in the brains of P301S tau mice (PS19 model) and intracerebroventricular injection of HDAC6 ASO resulted in a 70% knockdown of HDAC6 protein in the brain. Despite a robust decrease in levels of HDAC6, no increase in tau acetylation was observed. Additionally, no change of tau phosphorylation or tau aggregation was detected upon the knockdown of HDAC6. We conclude that HDAC6 does not impact tau pathology in PS19 mice.